Vestibular-evoked extraocular potentials by air-conducted sound: Another clinical test for vestibular function - Chihara, Yasuhiro; Iwasaki, Shinichi; Ushio, Munetaka; Murofushi, Toshihisa (Clinical neurophysiology, 2007)
The purpose of this study was to identify an appropriate way to detect vestibular-evoked extraocular potentials (oVEMPs) produced by air-conducted sound stimulation in healthy subjects and to apply this test clinically in patients with various vestibular disorders. Ten healthy subjects were included in this study. Surface electromyographic (EMG) activity was recorded from active electrodes placed on the face just inferior to each eye. Stimulation with 0.1 ms clicks and 500 Hz short tone bursts was used to activate the vestibular end-organs in healthy subjects. We also tested 12 patients with unilateral vestibular disorders using 500 Hz short tone bursts. In healthy subjects, negative–positive biphasic responses with short latency by air-conducted click (the first negative peak latency = 8.8 ms and the following positive peak latency = 14.5 ms on the average) (oVEMP) were only identified beneath the eye contralateral to the stimulating ear. On the other hand, stimulation with 500 Hz short tone bursts evoked negative–positive biphasic responses (the first negative peak latency = 10.5 ms and the following positive peak latency = 15.9 ms on the average) on both ipsilateral and contralateral eyes, while responses were contralateral eye-dominant. Contralateral eye responses by 500 Hz short tone bursts had higher response prevalence and larger amplitudes than clicks. In patients, oVEMPs evoked by the affected side stimulation tended to decrease or lacked a response. The presence of oVEMPs and cVEMPs coincided well in patients when 500 Hz short tone bursts were presented. oVEMPs can be evoked using air-conducted 500 Hz tone burst and are best recorded contralaterally on upgaze. oVEMPs by air-conducted sounds could be a useful alternative clinical test for patients with vestibular lesions.